CD81-Dependent Binding of Hepatitis C Virus E1E2 Heterodimers - Cocquerel, Laurence (American Society for Microbiology, 2003)
Hepatitis C virus (HCV) is the leading cause of chronic liver disease worldwide. HCV is also the major cause of mixed cryoglobulinemia, a B-lymphocyte proliferative disorder. Direct experimentation with native viral proteins is not feasible. Truncated versions of recombinant E2 envelope proteins, used as surrogates for viral particles, were shown to bind specifically to human CD81. However, truncated E2 may not fully mimic the surface of HCV virions because the virus encodes two envelope glycoproteins that associate with each other as E1E2 heterodimers. Here we show that E1E2 complexes efficiently bind to CD81 whereas truncated E2 is a weak binder, suggesting that truncated E2 is probably not the best tool with which to study cellular interactions. To gain better insight into virus-cell interactions, we developed a method by which to isolate E1E2 complexes that are properly folded. We demonstrate that purified E1E2 heterodimers bind to cells in a CD81-dependent manner. Furthermore, engagement of B cells by purified E1E2 heterodimers results in their aggregation and in protein tyrosine phosphorylation, a hallmark of B-cell activation. These studies provide a possible clue to the etiology of HCV-associated B-cell lymphoproliferative diseases. They also delineate a method by which to isolate biologically functional E1E2 complexes for the study of virus-host cell interaction in other cell types.